The Influence of Technology Use on the Spiritual Closeness of IAKN Kupang Students - Miliani Selfina Pada; Mefi Osingra Eky; Neri James Rivaldi Seran; Miadi Nubatonis; Yefta Ibrahim Ndaparoka; Mirna Kabu; Novita Kridayanti Ledoh; Adriana Indra Santi Sole (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to analyze and understand the influence of technology on the spiritual closeness of students at the Christian State Institute (IAKN) Kupang. The rapid development of digital technology has brought changes to various aspects of life, including the spiritual lives of Christian students. This research uses a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation involving active students of IAKN Kupang selected through purposive sampling. The findings indicate that technology has a significant influence on students’ spiritual closeness, both positively and negatively. Positive impacts include easier access to devotional materials, digital Bibles, online worship services, and spiritual content that supports faith development. On the other hand, negative impacts are reflected in reduced prayer time, declining spiritual discipline, and increased distractions due to excessive social media use. This study concludes that technology can serve as a means of supporting students’ spiritual growth when used wisely, in balance, and based on Christian values.